The Lack of a Strong and Accountable Public Procurement Ecosystem in West Papua to Prevent Corruption - Sopian Sopian; Bagas Johantri; Rachma Aprilia (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
West Papua has a relatively high risk of corruption during the implementation of its public procurement. It is critical to recognize that public procurement business processes are analyzed as an ecosystem with interactions between actors. This research aims to determine the need for a conducive ecosystem for public procurement (PBJP) in the West Papua province and propose recommendations for improving or increasing the credibility of public procurement. This research is qualitative because primary data are obtained through interviews and Forum Group discussions with selected participants. The results of the study show that the public procurement ecosystem consists of Budget User Authorities (KPA) or Contract Officers (PPK), Working Units for Public Procurement (UKPBJ), Vendors, Internal Control, and  Regulators who are credible procurement actors as focal offers. Examining each actor's issues has led to the conclusion that to boost the credibility of public procurement goals. It is necessary to strengthen leadership commitment, improve the quality of human resources, and simplify laws. The research findings are expected to assist practitioners and policymakers in understanding why there is a lack of public procurement ecosystem in West Papua and propose the necessary corrective policies.